Analysis of Infectious Diseases Spreading Process and ICT-Based Management System - Jo, Hyun Ju; Moon, Sung Gye; Lee, Bong Gyou (International Journal of Management and Sustainability, 2016)
Recently, as an interest in strongly contagious infectious diseases such as MERS increases, proper infectious disease management systems using ICT have been discussed. Particularly in Korea, the process-centered measures on the basis of ICT infrastructure and the internet of things are under discussion. However, studies on these are very rare. This study aims to propose an infectious disease management system in which ICT is incorporated into each process of the spread of infectious diseases. The scope of analysis is limited to the infectious diseases that flow from a country into the other country through air transportation. The process encompassing from the entry to the eradication of an infectious disease is classified into 5 stages (airport, transportation of patients, medical institutions, self-isolation, and waste disposal), and a journey map is suggested. Subsequently, an efficient infectious disease management system in which ICT is introduced to each stage is proposed. This study has significance in that it has unprecedentedly analyzed the entire spreading process of infectious disease from the process-centered perspective, and is expected to suggest a new convergence direction of ICT.